Structure effect of the envelope coupled with heat reflective coating and phase change material in lowering indoor temperature. (September 2021) - Ling, Ziye; Zhang, Yixue; Fang, Xiaoming; Zhang, Zhengguo
Highlights: Integrated cooling with heat reflective coating(HRC) and phase change material(PCM). Effects of relative positions of HRC and PCM on the indoor temperature. An insulation air gap can strengthen the functioning of the HRC and PCM. Investigates the effects of thermal conductivity of PCMs on thermal insulation. Explores the effects of different thick air layer and PCM boards. Abstract: The building envelopes that integrate heat reflective coatings (HRCs) and phase change materials (PCMs) can block solar radiation from outdoors and have a high thermal inertia, which helps lower the indoor temperature and save the cooling energy costs. However, an inappropriate combination of the two materials could lead to a worse cooling performance. This paper studies the cooling performance of a wall which is coated with the HRC, coupled with a cavity filling the PCM and insulation materials. This work intends to find out the optimal way of integrating the HRC and PCM together to improve the passive cooling performance of the envelope. The effects of the relative positions of HRC and PCM boards on the indoor temperature are studied by comparing 15 combinations of HRCs and PCMs. The results show that the HRC coated on the exterior surface of the wall can block the radiation heat more efficiently than that on the interior surface. An insulation layer between the HRC and PCM is essential to improve the thermal regulation performance of the wall. The insulation layer avoids the fast heat conduction through the PCM and decouples the roles of the HRC as a radiation reflector and the PCM as a thermal storage medium. The thermal conductivity of PCMs, the thickness of PCM layers as well as insulation air gap are also changed to investigate their influence on temperature fluctuations. The RT31/SiO2 (0.09 W/m K) can effectively reduce the indoor temperature by up to 3.6°C compared with the RT31/expanded graphite (EG) (1.25 W/m K). The optimum thickness of both PCM cavity and air cavity are no more than 8 mm. The work provide an insight into the optimal combination of the PCM and HRC in the building envelope for passive cooling.